A facile, versatile hydrogel bioink for 3D bioprinting benefits long-term subaqueous fidelity, cell viability and proliferation. Issue 3 (14th June 2021) - Chen, Hongqing; Fei, Fei; Li, Xinda; Nie, Zhenguo; Zhou, Dezhi; Liu, Libiao; Zhang, Jing; Zhang, Haitao; Fei, Zhou; Xu, Tao
Abstract: Both of the long-term fidelity and cell viability of three-dimensional (3D)-bioprinted constructs are essential to precise soft tissue repair. However, the shrinking/swelling behavior of hydrogels brings about inadequate long-term fidelity of constructs, and bioinks containing excessive polymer are detrimental to cell viability. Here, we obtained a facile hydrogel by introducing 1% aldehyde hyaluronic acid (AHA) and 0.375% N -carboxymethyl chitosan (CMC), two polysaccharides with strong water absorption and water retention capacity, into classic gelatin (GEL, 5%)–alginate (ALG, 1%) ink. This GEL–ALG/CMC/AHA bioink possesses weak temperature dependence due to the Schiff base linkage of CMC/AHA and electrostatic interaction of CMC/ALG. We fabricated integrated constructs through traditional printing at room temperature and in vivo simulation printing at 37°C. The printed cell-laden constructs can maintain subaqueous fidelity for 30 days after being reinforced by 3% calcium chloride for only 20 s. Flow cytometry results showed that the cell viability was 91.38 ± 1.55% on day 29, and the cells in the proliferation plateau at this time still maintained their dynamic renewal with a DNA replication rate of 6.06 ± 1.24%. This work provides a convenient and practical bioink option for 3D bioprinting in precise soft tissue repair.